2014
DOI: 10.1080/10420150.2014.984612
|View full text |Cite
|
Sign up to set email alerts
|

Raman studies on the effect of multiple-energy ion implantation on single-crystal hexagonal boron nitride

Abstract: Single energy ion implantation of hexagonal boron nitride (h-BN) at various fluences and keV energies has shown that there is a change in the local symmetry of the crystal from hexagonal to the cubic (c-BN) symmetry. These conclusions have been primarily based on Raman scattering (RS) and Fourier transform infrared spectroscopy. Transmission electron microscopy (TEM) analyses have been a challenge because the sample preparation for cross-sectional study of both the polycrystalline substrates and single-crystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…Hardness testing of the implanted BN samples was carried out using the FM-700 micro- Cubic BN with nanoscale particles tends to show the LO phonon modes [4,[7][8], shifted to lower energies, as we see here after implantation as broad peaks around 1300 cm -1 ; this peak indicates a phase change to cubic-BN, as reported in detail before [1][2][3][4][5].…”
Section: Micro-indentationsupporting
confidence: 68%
See 2 more Smart Citations
“…Hardness testing of the implanted BN samples was carried out using the FM-700 micro- Cubic BN with nanoscale particles tends to show the LO phonon modes [4,[7][8], shifted to lower energies, as we see here after implantation as broad peaks around 1300 cm -1 ; this peak indicates a phase change to cubic-BN, as reported in detail before [1][2][3][4][5].…”
Section: Micro-indentationsupporting
confidence: 68%
“…Cubic BN is synthesized in industrial quantities under pressure, but it has been shown that the implantation of light ions into h-BN can trigger a phase change to c-BN, which forms a thin layer of nanoparticles (9nm) within the implanted region. From Raman, X-ray and infrared analyses [1][2][3][4][5] there is an optimum ion fluence for He + , Li + , B + and N + which decreases as the ion mass increases. The creation of interstitial defects is thought to tip the structure from hexagonal layers to the tetrahedral cubic form.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work we use moderate energy B ion implantation as a technique to promote h-BN to c-BN nucleation and characterize samples using TEM. stretching within the basal plane [36], [43]. Figure 3 (b) represents the Raman spectrum for the sample implanted with 150 keV B to a fluence of 1.5×10 15 ions/cm 2 .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Cubic BN with size >500 nm showstwo phonon modes: the Transverse Optical (TO) line which occurs at ~1057 cm -1 and the Longitudinal Optical (LO) line which occurs at ~1305 cm -1 [45].If the c-BN contains micron and nano-size crystals, the Raman spectrum will display a TO mode at 1057 cm -1 and LO modes at 1305 cm -1 with an unstructured broad feature located near the LO phonon mode centred around 1290 cm -1 . When the specimen is made of nanocrystals (<100nm) the TO mode for c-BN disappears, while the LO mode peak broadens and shifts to a frequency of about 1290 cm -1 .The experimental measurements and analyses for the changes in c-BN Raman lineshape for c-BN with various particle sizes have been carried out and discussed in previous work [36]. Parayanthal et al [46]using the Spatial Correlation Model (SCM) explained the effect of particle size on the changes in the Raman lineshape broadening and symmetry.…”
Section: Haadf-stem and Hrtemmentioning
confidence: 99%